2005
DOI: 10.3168/jds.s0022-0302(05)73040-x
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Feed Delivery Affects the Behavior of Lactating Dairy Cows

Abstract: The objectives of this study were to examine how frequency of feed delivery affects 1) the behavior of group-housed and group-fed dairy cows and 2) the extent of feed sorting. These objectives were tested in two experiments. In each experiment, 48 lactating Holstein cows, split into groups of 12, were subjected to each of 2 treatments (over 10-d periods) in a cross-over design. The treatments for the first experiment were 1) delivery of feed once per day (1x) and 2) delivery of feed twice per day (2x). Treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
122
3
8

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 206 publications
(147 citation statements)
references
References 24 publications
14
122
3
8
Order By: Relevance
“…Differences between indoor AMS voluntary traffic across time are likely related to feed bunk activity as per where feed bunk activity was evenly distributed throughout 24 h alongside milking robot utilization. This hypothesis is supported by DeVries et al (2005) who found an increase in feeding activity and diurnal feeding pattern during the early morning when PMR was offered four times per day as compared with two times per day. Though, the evenly distributed milking robot utilization achieved in the study was likely influenced by the 6 h (four feeding periods per day) concentrate feeding regime, along with the PMR offered in this system, whereby each animal could access a new allocation of concentrate in each of the four feeding periods.…”
Section: Feed Factorsmentioning
confidence: 65%
“…Differences between indoor AMS voluntary traffic across time are likely related to feed bunk activity as per where feed bunk activity was evenly distributed throughout 24 h alongside milking robot utilization. This hypothesis is supported by DeVries et al (2005) who found an increase in feeding activity and diurnal feeding pattern during the early morning when PMR was offered four times per day as compared with two times per day. Though, the evenly distributed milking robot utilization achieved in the study was likely influenced by the 6 h (four feeding periods per day) concentrate feeding regime, along with the PMR offered in this system, whereby each animal could access a new allocation of concentrate in each of the four feeding periods.…”
Section: Feed Factorsmentioning
confidence: 65%
“…Reduced sorting is considered beneficial because it diminishes diurnal variation of nutrient intake (DeVries et al, 2005). The results of this experiment suggest that a ration with a particle size distribution similar to the Medium ration minimizes sorting activity and does not compromise DMI.…”
Section: Resultsmentioning
confidence: 82%
“…The self-feed treatment differed from the other treatments with regard to the feed delivery system. It is possible that reduced competition at the feed face (O'Driscoll et al, 2008c) could have improved access to feed for all cows in this treatment (DeVries et al, 2005), and thus helped to maximise performance post partum. However, further work is necessary to investigate whether this feeding strategy could provide benefits for cow production performance in general.…”
Section: Discussionmentioning
confidence: 99%